The crucial years : the essential guide to mental health & modern puberty in middle childhood (ages 6-12) - Ziegler, Sheryl (Harvest, an imprint of William Morrow, 2025)
A "guide for parents and caregivers, this book offers insights, strategies, and understanding to navigate middle childhood (ages 6-12). Dr. Sheryl Gonzalez Ziegler, a seasoned clinical psychologist and mother, highlights ways to foster resilience, encourage open communication, and build lasting connections during this crucial period"--